2020
DOI: 10.1021/acs.est.0c03285
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Spatial and Seasonal Trends of Methylmercury Exposure Pathways of Arctic Seabirds: Combination of Large-Scale Tracking and Stable Isotopic Approaches

Abstract: Despite the limited direct anthropogenic mercury (Hg) inputs in the circumpolar Arctic, elevated concentrations of methylmercury (MeHg) are accumulated in Arctic marine biota. However, the MeHg production and bioaccumulation pathways in these ecosystems are not completely unravelled. We measured Hg concentrations and stable isotope ratios of Hg, carbon and nitrogen in feathers and blood of geolocator-tracked little auk Alle alle from five Arctic breeding colonies. The wide-range spatial mobility and tissue-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 83 publications
(222 reference statements)
1
12
0
Order By: Relevance
“…This is one of few studies investigating effects of contamination on breeding parameters in relation to non-breeding distribution. The pattern with winter Hg concentrations remaining consistently higher than in summer has been confirmed by other studies and for other migrating alcid species (Fort et al 2016, Renedo et al 2020, Albert et al 2021a). Fort et al (2016) examined inter-annual changes in mercury (Hg) contamination in little auks and their zooplankton prey in East Greenland and found an increasing trend in summer contamination (3.4% per year over the 8 yr period, 2006−2014), whereas the winter exposure to Hg decreased over the same period.…”
Section: Consequences Of Migration Strategies For Contaminant Burdenssupporting
confidence: 84%
See 1 more Smart Citation
“…This is one of few studies investigating effects of contamination on breeding parameters in relation to non-breeding distribution. The pattern with winter Hg concentrations remaining consistently higher than in summer has been confirmed by other studies and for other migrating alcid species (Fort et al 2016, Renedo et al 2020, Albert et al 2021a). Fort et al (2016) examined inter-annual changes in mercury (Hg) contamination in little auks and their zooplankton prey in East Greenland and found an increasing trend in summer contamination (3.4% per year over the 8 yr period, 2006−2014), whereas the winter exposure to Hg decreased over the same period.…”
Section: Consequences Of Migration Strategies For Contaminant Burdenssupporting
confidence: 84%
“…Fort et al (2016) examined inter-annual changes in mercury (Hg) contamination in little auks and their zooplankton prey in East Greenland and found an increasing trend in summer contamination (3.4% per year over the 8 yr period, 2006−2014), whereas the winter exposure to Hg decreased over the same period. Renedo et al (2020) investigated Hg concen-trations in little auks from 5 Atlantic Arctic breeding colonies and found a consistent latitudinal pattern with birds from northern Arctic regions (northern Barents Sea) exposed to lower Hg concentrations compared to those from more southern regions (Labrador Sea).…”
Section: Consequences Of Migration Strategies For Contaminant Burdensmentioning
confidence: 90%
“…black-legged kittiwake, Brünnich's guillemot, common eider and little auk). Then, we predicted that (1) seabirds with low fidelity to a wintering ground from one year to the other show more variable Hg contamination in comparison to those showing similar inter-annual winter distributions and (2) seabird wintering distribution affects Hg contamination (Renedo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies focussed on these issues have the potential to be extrapolated to other groups of organisms. Circumpolar High Arctic breeding range (Wojczulanis-Jakubas et al 2011b) Gene flow between populations Circumpolar High Arctic breeding range (Wojczulanis-Jakubas et al 2014c, 2015b Ecotoxicology Transfer of pollution from sub-Arctic and temperate zone non-breeding areas to the High Arctic Breeding in the High Arctic and wintering in the sub-Arctic and temperate zones (Fort et al 2013;Renedo et al 2020;Pacyna-Kuchta et al 2020;Albert et al 2021) Microbiology Bacterial resistance to antibiotics Breeding in a pristine, antibiotic-free environment (Literak et al 2014) Climate change Link between environmental conditions, population size, distribution, reproductive performance and survival Endemic Arctic species are especially vulnerable to the consequences of climate change (Jakubas et al , 2016(Jakubas et al , 2017(Jakubas et al , 2020(Jakubas et al , 2022Kwasniewski et al 2012Kwasniewski et al , 2010Karnovsky et al 2010;Grémillet et al 2012;Hovinen et al 2014a, b;Ramírez et al 2017;Amélineau et al 2019) Scenarios of future foraging habitat suitability Endemic Arctic species are especially vulnerable to the consequences of climate change (Jakubas et al 2017;Clairbaux et al 2019)…”
Section: Discussionmentioning
confidence: 99%
“…It moults twice a year, with different feather types being grown at different times of the year and locations (breeding/non-breeding grounds), which allows investigation of the exposure of Little Auks to elements throughout the annual cycle (Fort et al 2013). Recent studies have revealed spatial and temporal variations in Hg concentrations in Little Auks, indicating greater exposure during the non-breeding period in the wintering areas than during the breeding season (Renedo et al 2020;Pacyna-Kuchta et al 2020;Albert et al 2021). Although for now, overall Hg concentrations in Little Auks are relatively low compared to other Arctic seabirds (Albert et al 2021), females with high Hg levels tend to lay smaller eggs (Fort et al 2014).…”
Section: Indicator Of Environmental Contaminationmentioning
confidence: 99%